Regular soccer training improves pulmonary diffusion capacity in 6 to 10 year old boys - Dridi, R.; Dridi, N.; Gmada, N.; Laher, I.; Saeidi, A.; Granacher, U.; Zouhal, H. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Soccer is one of the most attractive sports around the globe for children and adolescents, and the benefits of soccer training are often shown. Due to the intermittent character of soccer with random changes between high-intensity activity and low-intensity play, athletes` aerobic (respiratory) capacity is specifically stimulated. However, little is known about the effects of regular soccer practice on pulmonary diffusion capacity (TL) in young players, even though it is the most popular sport in the world.